The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acschembio.0c00453
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Method for the Unambiguous Profiling of Cellular Dynamic Glycosylation

Abstract: Various biological processes at the cellular level are regulated by glycosylation which is a highly micro-heterogeneous post-translational modification (PTM) on proteins and lipids. The dynamic nature of glycosylation can be studied through bio-orthogonal tagging of metabolically engineered nonnatural sugars into glycan epitopes. However, this approach possesses a significant drawback due to nonspecific background reactions and ambiguity of non-natural sugar metabolism. Here we report a tag-free strategy for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…In MOE experiments, we and others have observed that chemically modified GalNAc analogs can be elaborated by downstream glycosylation. [27][28][29]36,37 As demonstrated in Figure 2E and Supporting Information Figure S3A, B, extension of the GalNAc analogs GalN6yne, GalNAz, and GalNAzMe could be observed in our MOE systems by virtue of defined HCD fragment ions. It is currently not known whether downstream glycosylation of these analogs proceeds with the same fidelity as for native GalNAc.…”
Section: Analysis Of Caged Glycopeptides Enriched From Complex Cell Lysatesmentioning
confidence: 55%
See 1 more Smart Citation
“…In MOE experiments, we and others have observed that chemically modified GalNAc analogs can be elaborated by downstream glycosylation. [27][28][29]36,37 As demonstrated in Figure 2E and Supporting Information Figure S3A, B, extension of the GalNAc analogs GalN6yne, GalNAz, and GalNAzMe could be observed in our MOE systems by virtue of defined HCD fragment ions. It is currently not known whether downstream glycosylation of these analogs proceeds with the same fidelity as for native GalNAc.…”
Section: Analysis Of Caged Glycopeptides Enriched From Complex Cell Lysatesmentioning
confidence: 55%
“…However, recent findings suggest that monosaccharide analogs are incorporated into various glycan sub-types without a notable chain-terminating effect. 28,29,36,37…”
Section: Analysis Of Caged Glycopeptides Enriched From Complex Cell Lysatesmentioning
confidence: 99%
“…Epimerization substantially decreases the glycan specificity while enhancing the labeling efficiency of certain MOE reagents and can be suppressed by careful choice of the chemical modification. 10 12 Once biosynthesized, the derivatives of UDP-GalNAc and UDP-GlcNAc can be used as substrates by cellular GTs, including the large polypeptide GalNAc transferase (GalNAc-T) family in the secretory pathway and a myriad of GlcNAc transferases in several cellular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…This is useful for studying endogenous sugar metabolism. 110 However, it complicates most applications of MCRs. Fortunately, individual salvage pathways exhibit some amount of substrate selectivity.…”
Section: Considerations and Limitations Of Mcrsmentioning
confidence: 99%
“…This was exemplified in recent work from the Kohler lab. 110 Here, efforts to generate a probe-free technique for the identification of glycoproteins illuminated the vast metabolic cross talk that interconverts GalNaz, GlcNAz and ManNAz. Additionally, there is still no universal MS workflow that generates site, structure, and biological context in one mega experiment.…”
Section: Considerations and Limitations Of Mcrsmentioning
confidence: 99%